Power Control Algorithm Based on Normalized Utility Function Research - Xiang Yu; Xiaoyin Zhang; Lei Liu (Dianxin kexue)
Power control is one of the key technologies of cognitive radio technology. Distributed power control problem can be converted into non-cooperative game to solve the problem. Combining with the characteristics of cognitive radio, a new type S utility function was put forwarded, the normalized form was applied, and the existence and uniqueness of the Nash equilibrium were proved. Simulation results show that the algorithm is not restricted by system modulation mode, and reduces the computational complexity, and has faster convergence speed. The fairness between the users was taken into account, to a certain extent, and the users can share channel resources fairly.